Loan types, leverage, and savings behaviour of Danish households - Andreas Kuchler (Danmarks Nationalbank, 2015)
Using Danish household level data, we find that a relatively large share of total interest-only mortgage debt is held by families with few liquid assets and high loan to value ratios. This may arise because families with interest-only loans do not fully use the lower instalments to increase their savings or to amortise more expensive debt. This is in particular the case for the families who choose interest-only loans with a variable interest rate, which is the most common loan type in Denmark, and the largest difference is found for those families who have the lowest savings propensity, and those with a high loan to value ratio. Furthermore, first time borrowers choosing interest-only loans take loans of higher initial sizes and have higher loan to value ratios than first time borrowers choosing amortising loans.
Keywords: D14; E21; G21; R31; 330; Mortgage loans; loan types; savings; financial stability